Plerixafor and resatorvid inhibit hepatitis B virus in vitro by upregulating elongation factor Tu GTP-binding domain containing 2 - Cai, Jinyuan; Li, Yuwen; Hu, Pingping; Xu, Ruirui; Yuan, Hui; Zhang, Wen; Feng, Tiantong; Liu, Rui; Li, Wenting; Zhu, Chuanlong (Frontiers in Cellular and Infection Microbiology, 2023)
Background An increase in the demand for a functional cure has accelerated research on new methods of therapy for chronic hepatitis B, which is mainly focused on restoring antiviral immunity for controlling viral infections. Previously, we had described elongation factor Tu GTP-binding domain containing 2 (EFTUD2) as an innate immune regulator and suggested that it might be an antiviral target. Methods In this study, we generated the Epro-LUC-HepG2 cell model for screening compounds that target EFTUD2. Plerixafor and resatorvid were screened from 261 immunity and inflammation-related compounds due to their ability to highly upregulate EFTUD2. The effects of plerixafor and resatorvid on hepatitis B virus (HBV) were examined in HepAD38 cells and HBV-infected HepG2-NTCP cells. Results The dual-luciferase reporter assays showed that the EFTUD2 promoter hEFTUD2pro-0.5 kb had the strongest activity. In Epro-LUC-HepG2 cells, plerixafor and resatorvid significantly upregulated the activity of the EFTUD2 promoter and the expression of the gene and protein. In HepAD38 cells and HBV-infected HepG2-NTCP cells, treatment with plerixafor and resatorvid strongly inhibited HBsAg, HBV DNA, HBV RNAs, and cccDNA in a dose-dependent manner. Furthermore, the anti-HBV effect was enhanced when entecavir was administered along with either of the previous two compounds, and the effect could be blocked by knocking down EFTUD2. Conclusion We established a convenient model for screening compounds that target EFTUD2 and further identified plerixafor and resatorvid as novel HBV inhibitors in vitro. Our findings provided information on the development of a new class of anti-HBV agents that act on host factors rather than viral enzymes.